1989
DOI: 10.1123/jsep.11.1.65
|View full text |Cite
|
Sign up to set email alerts
|

An In-depth Study of Former Elite Figure Skaters: II. Sources of Enjoyment

Abstract: This study investigated the sources of sport enjoyment for elite figure skaters. These elite athletes were 26 former national championship competitors who currently coach figure skating. The skaters were interviewed and answered an open-ended question asking them for their sources of enjoyment during the most competitive phase of their skating careers. Each source of enjoyment mentioned was probed to obtain an in-depth understanding of the source. The data, 418 quotes, were drawn from verbatim transcriptions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
98
0
9

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(108 citation statements)
references
References 0 publications
1
98
0
9
Order By: Relevance
“…Ostensibly, the activity is enjoyable in its own right and is not engaged in for the derivation of external rewards and benefits. The aforementioned In general, a number of studies examining flow across a variety of contexts have demonstrated that flow is an optimal and thoroughly enjoyable experience (Csikszentmihalyi and Lefevre, 1989;Jackson, 1992Jackson, , 1996Mannell, Zuzanek, and Larson, 1988;Scanlan, Stein, and Ravizza, 1989). It is important that such investigations be extended to the context of exercise given the potential ramifications for the enhancement of physical and mental health.…”
Section: Flow State Scalementioning
confidence: 99%
“…Ostensibly, the activity is enjoyable in its own right and is not engaged in for the derivation of external rewards and benefits. The aforementioned In general, a number of studies examining flow across a variety of contexts have demonstrated that flow is an optimal and thoroughly enjoyable experience (Csikszentmihalyi and Lefevre, 1989;Jackson, 1992Jackson, , 1996Mannell, Zuzanek, and Larson, 1988;Scanlan, Stein, and Ravizza, 1989). It is important that such investigations be extended to the context of exercise given the potential ramifications for the enhancement of physical and mental health.…”
Section: Flow State Scalementioning
confidence: 99%
“…The present study attempted to alleviate a portion of these inherent problems by allowing a structured dialog to occur as athletes responded to the mental strategy items as well as framing the items in terms of both general and situation-specific use. Several authors contend that with proper research methodology and controls, honest responses and comparatively rich descriptive information may be generated through the use of this method (Martens, 1987;Scanlan, Stein, & Ravizza, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…As theorized by Scanlan et al, many SCM studies with youth found enjoyment was the strongest predictor of commitment (e.g., Stein & Scanlan, 1992;Scanlan, Ravizza, & Stein, 1989). When investigating the SCM with youth tennis players, Weiss et al (2001) modified the original model to further understand the impact of enjoyment.…”
Section: Variables In the Modelmentioning
confidence: 99%